2009
DOI: 10.1101/gad.1882109
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming inhibition in the spindle checkpoint: Figure 1.

Abstract: Spindle checkpoint silencing is a critical step during mitosis that initiates chromosome segregation, yet surprisingly little is known about its mechanism. Protein phosphatase I (PP1) was shown recently to be a key player in this process, and in this issue of Genes & Deverlopment, Akiyoshi and colleagues (pp. 2887–2899) identify budding yeast Fin1p as a kinetochore-localized regulator of PP1 activity toward checkpoint targets. Here we review recent mechanistic insights and propose a working model for spind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 57 publications
2
24
0
Order By: Relevance
“…Silencing the mitotic checkpoint, just like activating the checkpoint, involves events at two venues: at kinetochores and in the cytoplasm (23,46). "Wait anaphase" signals (predominantly C-MAD2) need to be terminated at kinetochores that are fully attached with spindle microtubules and bioriented with tension.…”
Section: Trip13 Is a Novel Mitotic Checkpoint-silencing Protein-mentioning
confidence: 99%
“…Silencing the mitotic checkpoint, just like activating the checkpoint, involves events at two venues: at kinetochores and in the cytoplasm (23,46). "Wait anaphase" signals (predominantly C-MAD2) need to be terminated at kinetochores that are fully attached with spindle microtubules and bioriented with tension.…”
Section: Trip13 Is a Novel Mitotic Checkpoint-silencing Protein-mentioning
confidence: 99%
“…In human cells, checkpoint proteins are stripped from the outer kinetochore upon microtubule attachment and transported to spindle poles in a dynein-dependent fashion [29]. This is thought to be one way vertebrate cells silence the spindle checkpoint, although it is not essential for silencing [30]. However, there is no evidence that dynein is involved in checkpoint protein targeting in yeast mitosis [31].…”
Section: Resultsmentioning
confidence: 99%
“…p31 comet does not appear to be conserved in all species with Mad2-like proteins (Habu et al 2002), and the involvement of PP1 in checkpoint silencing has only recently been demonstrated in fungi (Pinsky et al 2009;Vanoosthuyse and Hardwick 2009a). Importantly, whether the p31 comet and PP1-dependent mechanisms are sensitive to kinetochoremicrotubule attachment status is currently unclear, and it is possible that these mechanisms operate to limit or inactivate the checkpoint signal in the cytoplasm (Vanoosthuyse and Hardwick 2009b). For PP1, one study has suggested a potential role in dynein-mediated removal of checkpoint proteins (Whyte et al 2008).…”
Section: Discussionmentioning
confidence: 99%